1999
DOI: 10.1021/bi990412o
|View full text |Cite
|
Sign up to set email alerts
|

Substrate and Inhibitor-Induced Conformational Changes in the Structurally Related Enzymes UDP-N-Acetylglucosamine Enolpyruvyl Transferase (MurA) and 5-Enolpyruvylshikimate 3-Phosphate Synthase (EPSPS)

Abstract: UDP-N-acetylglucosamine enolpyruvyl transferase (MurA) and 5-enolpyruvylshikimate 3-phosphate synthase (EPSPS) have both a unique three-dimensional topology and overall reaction mechanism in common. In the case of MurA, the substrate-free, unliganded protein exhibits an "open" conformation. Upon binding of substrates, the protein forms a much more tightly packed so-called "closed" form following an induced fit mechanism. In this closed form, the substrates are properly positioned for catalysis. On the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 29 publications
(53 reference statements)
1
41
0
Order By: Relevance
“…1B) in the presence of a saturating amount of UDP-GlcNAc (1 mM) in 100 mM triethanolamine-HCl at pH 8.0. Binding of UDP-GlcNAc to MurA has been shown to induce a conformational change resulting in an increased affinity toward PEP (25). The inactivation rate of MurA with fosfomycin is also dependent upon UDP-GlcNAc (8).…”
Section: Resultsmentioning
confidence: 99%
“…1B) in the presence of a saturating amount of UDP-GlcNAc (1 mM) in 100 mM triethanolamine-HCl at pH 8.0. Binding of UDP-GlcNAc to MurA has been shown to induce a conformational change resulting in an increased affinity toward PEP (25). The inactivation rate of MurA with fosfomycin is also dependent upon UDP-GlcNAc (8).…”
Section: Resultsmentioning
confidence: 99%
“…A partial conformational change upon S3P binding is supported by the results of Stepanek [16], who found that monoclonal antibodies could be raised against the binary EPSPS b S3P complex, distinct from antibodies that recognized the enzyme alone. Also, Krekel et al [17] found that S3P binding did not increase the dissociation constant of a monoclonal antibody raised against EPSP synthase, implying that S3P alone did not induce a full conformational change that disrupted the recognition of the antibody. This contrasted with the results of their mass spectrometric analysis, and could be explained by hypothesizing that S3P induced only a partial conformational change that allowed the antibody access to its epitope while restricting the access of trypsin to proteolytic cleavage sites.…”
Section: Discussionmentioning
confidence: 99%
“…On ligand binding, the MurA tertiary structure changes from the ''open'' form of the enzyme to the ''closed'' form, in which the two domains rearrange substantially into a tightly packed conformation (13). Using limited tryptic digestion and matrix-assisted laser desorption ionizationtime-of-flight mass spectroscopy, Krekel et al (14) have suggested that binding of S3P in combination with glyphosate also stabilizes EPSPS in a closed conformation. In addition, fluorescence spectroscopy studies imply that the association of glyphosate with the EPSPS-S3P binary complex induces a substantial conformational change in the enzyme (15).…”
Section: Methodsmentioning
confidence: 99%